Response of Resistant Malignant Tumors to Neutron Therapy; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Musabaeva L. I. (Radiation Technologies in Medicine, 2015)
Title screen